Scientific, Technological and Legal Background of Creating Integrated Biotic Databases - Nowak, Maciej (Wydawnictwo Naukowe UAM, 2015)
This monograph consists of ten original chapters which explore topics that are very important today, i.e. the design of GIS databases, the management of these databases and factors that determine the availability of spatial data. Increasingly, these issues, which are associated with abiotic databases, affect numerous emerging resources of data about animate nature. The monograph also contains information on legal matters concerning access to spatial information or issues related to the INSPIRE directive, which provides a basis for creating national laws concerning the infrastructure of spatial information. Much attention was also paid to examples of using research studies that generate great resources of spatial data, which are used to establish databases and make them available, for example, on web portals. This monograph presents several examples of how databases are created and how they function, including the Polish Biodiversity Information Network (PL: Krajowa Sieć Informacji o Bioróżnorodności) and Open-Access Bio- and Geodiversity Database for Silesia Province (PL: Ogólnodostępna Baza Danych Bio- i Georóżnorodności Województwa Śląskiego).